Effect of Acupressure on Symptoms of Postoperative Ileus After Cesarean Section - Faezeh Abadi; Maryam Shahabinejad; Foziyeh Abadi; Majid Kazemi (Medical Association of Pharmacopuncture Institute, 2017)
Postoperative ileus (POI) is a common complication after most abdominal surgeries including cesarean section. It is associated with longer hospitalization and increased medical costs. This study is a randomized controlled trial investigating the effect of acupressure, and low-cost noninvasive traditional treatment, on POI symptoms after cesarean section. A total of 120 patients were randomly divided into two groups; the treatment group received two sessions of acupressure (an hour after attending the women's division; and 3 hours after the first session), each lasting 20 minutes. The time of flatus and defecation, time to presence of bowel sounds, and duration of postoperative bed rest were monitored. Patients in the treatment group had a shorter time to presence of bowel sounds compared with those in the control group (p < 0.001), as well as shorter time to first passage of flatus (p < 0.001) and shorter postoperative bed rest (p = 0.005). However, the time to first defecation was not statistically significant (p = 0.311). Acupressure has potential positive impacts on attenuating POI symptoms after cesarean section, and can be used as a low-cost noninvasive nursing care to reduce POI incidence and intensity after cesarean section.